The effect of wudu therapy on sleep quality as a determinant of happiness and work productivity among college lecturers - Reza, Iredho Fani; Setiawan, Kiki Cahaya; Hadinata, Eko Oktapiya; Oktaviani, Nasywa Syahira; Kamilah, Salsabila Nur; Amanda, Zarnalia (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2024)
This study aims to examine the effect of wudu therapy on happiness, sleep quality, and work productivity in college lecturers. This type of research uses mixed methods with Embedded Design. Respondents of the study were active lecturers at four universities in South Sumatra, as determined by the Multistage Sampling Technique, which obtained N = 58 and was divided into 29 experimental groups and 29 control groups. The measurement of the study used the Sleep Quality Scale (reliability 0.81), the Muslim Spiritual Happiness Scale (internal consistency 8-9), and the Lecturer Work Productivity Scale (reliability 0.882). Data analysis techniques used path analysis techniques, Independent T-test analysis, and descriptive analysis with the help of IBM SPSS version 25. The main findings of this study found that wudu therapy indirectly affected happiness and work productivity through sleep quality as a mediator. Recommendations from this study provide new insights for implementing wudu therapy in Higher Education to improve the quality of Lecturers and further research development.